Acronictinae (Lepidoptera: Macroheterocera: Noctuidae) Demonstrate the Variable Role of Wing Venation in the Evolution of the Nymphalid Groundplan. Issue 2 (20th March 2018) - Schachat, Sandra R; Goldstein, Paul Z
Abstract: The nymphalid groundplan (NGP) is an idealized system used to classify and interpret wing pattern elements of butterflies. Nearly a century ago, the principles of the NGP were applied to the wing patterns of higher moths (Macroheterocera). Recent advances in phylogeny and in the comparative morphology of microlepidopteran wing pattern both suggest promise in revisiting the relevance of the NGP to the more conspicuous and derived groups of large Lepidoptera. In the noctuid subfamily Acronictinae, wing patterns include elements corresponding to the central symmetry system, discal (reniform) spot, and parafocal elements of the NGP. Wing patterns in this lineage are also consistent with the 'uniform wing-margin' model, which was hypothesized to explain the relationship between wing venation and color pattern, and which has been corroborated in various lineages of microlepidoptera. The uniform wing-margin model does not appear to hold for butterflies, however, and has not previously been evaluated in Macroheterocera. The finding that NGP-like wing patterns in Macroheterocera share features with microlepidoptera is consistent with convergence, i.e., with independent origins of 'the' NGP. Furthermore this finding suggests that such superficially similar (not strictly homologous) 'NGPs' may have arisen via different mechanisms corresponding to ancestral differences in the relationships between wing patterns wing venation, and can be differentiated on that basis.